Examining potential side effects of therapeutic hypothermia in experimental intracerebral hemorrhage. Issue 8 (August 2017) - Wowk, Shannon; Fagan, Kelly J; Ma, Yonglie; Nichol, Helen; Colbourne, Frederick
Studies treating intracerebral hemorrhage (ICH) with therapeutic hypothermia (TH) have shown inconsistent benefits. We hypothesized that TH's anti-inflammatory effects may be responsible as inflammatory cells are essential for removing degrading erythrocytes. Here, we subjected rats to a collagenase-induced striatal ICH followed by whole-body TH (∼33℃ for 11–72 h) or normothermia. We used X-ray fluorescence imaging to spatially quantify total and peri-hematoma iron three days post-injury. At three and seven days, we measured non-heme iron levels. Finally, hematoma volume was quantified on one, three, and seven days. In the injured hemisphere, total iron levels were elevated ( p  < 0.001) with iron increasing in the peri-hematoma region ( p  = 0.007). Non-heme iron increased from three to seven days (p  < 0.001). TH had no effect on any measure of iron ( p  ≥ 0.479). At one and three days, TH did not affect hematoma volume ( p  ≥ 0.264); however, at seven days there was a four-fold increase in hematoma volume in 40% of treated animals ( p  = 0.032). Thus, even when TH does not interfere with initial increases in total and non-heme iron or its containment, TH can cause re-bleeding post-treatment. This serious complication could partly account for the intermittent protection previously observed. This also raises serious concerns for clinical usage of TH for ICH.